A Single-Culture Bioprocess of Methanothermobacter thermautotrophicus to Upgrade Digester Biogas by CO2-to-CH4 Conversion with H2. (1st October 2013) - Martin, Matthew R.; Fornero, Jeffrey J.; Stark, Rebecca; Mets, Laurens; Angenent, Largus T.
Abstract : We optimized and tested a postbioprocessing step with a single-culture archaeon to upgrade biogas (i.e., increase methane content) from anaerobic digesters via conversion of CO2 into CH4 by feeding H2 gas. We optimized a culture of the thermophilic methanogen Methanothermobacter thermautotrophicus using: (1) a synthetic H2 /CO2 mixture; (2) the same mixture with pressurization; (3) a synthetic biogas with different CH4 contents and H2 ; and (4) an industrial, untreated biogas and H2 . A laboratory culture with a robust growth (dry weight of 6.4–7.4 g/L; OD600 of 13.6–15.4), a volumetric methane production rate of 21 L/L culture-day, and a H2 conversion efficiency of 89% was moved to an industrial anaerobic digester facility, where it was restarted and fed untreated biogas with a methane content of ~70% at a rate such that CO2 was in excess of the stoichiometric requirements in relation to H2 . Over an 8-day operating period, the dry weight of the culture initially decreased slightly before stabilizing at an elevated level of ~8 g/L to achieve a volumetric methane production rate of 21 L/L culture-day and a H2 conversion efficiency of 62%. While some microbial contamination of the culture was observed via microscopy, it did not affect the methane production rate of the culture.